Empowering Marginalized Communities through Social Entrepreneurship to Foster Inclusive Sustainable Economic Growth in Pakistan - Zohaib Hassan Sain; Aydin Anar Babayev; Elshad Yusifov (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This community-based program aims to strengthen the economic resilience of marginalized groups in Pakistan through a social entrepreneurship model that promotes inclusion, innovation, and long-term sustainable growth. The initiative responds to persistent socio-economic inequalities that limit opportunities for low-income populations, particularly women, youth, and rural communities. By integrating entrepreneurial training, financial literacy education, and community-based business incubation, the program equips participants with the skills needed to initiate and sustain micro-enterprises. The model emphasizes the use of local resources, socially responsible business practices, and community-led decision-making to ensure contextual relevance. Data collected through baseline assessments, participatory workshops, and post-program evaluations show significant improvement in participants’ entrepreneurial competencies, confidence, and engagement in local economic activities. Government officials, NGOs, and private-sector partners reported increased trust and willingness to collaborate with trained communities. Feedback from participants highlights enhanced motivation, improved financial knowledge, and stronger social networks. Overall, the program demonstrates that social entrepreneurship can be a powerful mechanism for inclusive economic development when combined with capacity building, community mobilization, and strategic partnerships. Findings offer insights for policymakers and academic researchers seeking scalable models to address marginalization and promote sustainable growth in Pakistan’s diverse socio-economic landscape.